2022
DOI: 10.1103/physrevlett.129.241102
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal Flux Loss due to Flux Emergence Explains why Solar Cycles Rise Differently but Decay in a Similar Way

Abstract: A striking feature of the solar cycle is that at the beginning, sunspots appear around mid-latitudes, and over time the latitudes of emergences migrate towards the equator. The maximum level of activity varies from cycle to cycle. For strong cycles, the activity begins early and at higher latitudes with wider sunspot distributions than for weak cycles. The activity and the width of sunspot belts increase rapidly and begin to decline when the belts are still at high latitudes. However, in the late stages of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently, the Babcock-Leighton mechanism (Babcock 1961;Leighton 1969), in which the tilted bipolar magnetic regions produce poloidal field in the sun, has received strong observational supports (Dasi-Espuig et al 2010;Kitchatinov & Olemskoy 2011;Priyal et al 2014;Cameron & Schüssler 2015). Including this process for the generation of the poloidal field, the Babcock-Leighton type dynamo models have produced great successes in providing many observational features of the solar magnetic cycle, including the grand minima (e.g., Choudhuri & Karak 2012;Karak & Miesch 2017;Cameron & Schüssler 2017;Lemerle & Charbonneau 2017;Inceoglu et al 2017;Biswas et al 2022).…”
mentioning
confidence: 99%
“…Recently, the Babcock-Leighton mechanism (Babcock 1961;Leighton 1969), in which the tilted bipolar magnetic regions produce poloidal field in the sun, has received strong observational supports (Dasi-Espuig et al 2010;Kitchatinov & Olemskoy 2011;Priyal et al 2014;Cameron & Schüssler 2015). Including this process for the generation of the poloidal field, the Babcock-Leighton type dynamo models have produced great successes in providing many observational features of the solar magnetic cycle, including the grand minima (e.g., Choudhuri & Karak 2012;Karak & Miesch 2017;Cameron & Schüssler 2017;Lemerle & Charbonneau 2017;Inceoglu et al 2017;Biswas et al 2022).…”
mentioning
confidence: 99%
“…Long-term modulations, including Gnevyshev-Ohl/Odd-Even rule (Charbonneau, 2001;Charbonneau et al, 2007) and grand minima (Charbonneau et al, 2004;Choudhuri and Karak, 2009;Passos et al, 2012 are naturally produced in these models. Variations within the cycle, like the amplitude-period anti-correlation (Charbonneau and Dikpati, 2000;Karak, 2010) and Waldmeier effect (Karak and Choudhuri, 2011;Biswas et al, 2022) are also reproduced. showed that a large variation in the Babcock-Leighton process can change the polar field abruptly and this can lead to double peaks in the following cycle.…”
Section: Babcock-leighton Dynamo Models For the Long-term Variationmentioning
confidence: 81%
“…In an extreme case, a largely reduced meridional circulation can trigger a Maunder-like grand Fig. 7 The trajectories of (a) annual sunspot number and (b) FWHM vs the central latitude of the annual spot distribution obtained from a dynamo simulation with buoyancy-induced flux loss (Biswas et al, 2022). Curves clearly show that the beginning phases of the cycles differ widely depending on their strengths but they decline in the same way irrespective of their strengths.…”
Section: Nonlinearities In the Dynamomentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in every cycle during the generation of the poloidal field, the memory of the polar field is degraded. The toroidal to poloidal component of the solar dynamo also involves some nonlinearities, which at least include the flux loss due to magnetic buoyancy in the formation of BMR (Biswas et al 2022), latitude quenching (Jiang 2020;Karak 2020), and tilt quenching (Jha et al 2020). The nonlinearity plays an important role in determining the memory of the polar field when the dynamo becomes supercritical.…”
Section: Introductionmentioning
confidence: 99%